SIKAP MASYARAKAT HUKUM ADAT BALI TERHADAP PUTUSAN MK NO. 46/PUU-VIII/2010 TERKAIT KEDUDUKAN ANAK LUAR KAWIN - Sukerti, Ni Nyoman; Agung Ariani, I Gst. Ayu; Sudantra, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p15, 2015)
This study aimed to determine the knowledge of indigenous people of Bali against the Constitutional Court No.46 / PUU-VII / 2010, meaning the Constitutional Court ruling related to the child outside the mating position, to identify and analyze the attitudes of indigenous communities Bali on the discharge of the Constitutional Court. This study is an empirical law with non-doctrinal approach (socio legal research). The results showed that indigenous people in general do not yet know Bali Court Decision No.46 / PUU-VII / 2010 was. Meaning beyond mating gives children the same rights as children born within marriage. Balinese people’s attitudes related to this decision, can be classified into two: 1. Most accept the decision of the reason; children outside the mating status to clear, the mother can claim responsibility for the biological father of the child, the child is no longer despised in the family and society. 2. small Sebagain reject reason; children outside mating can cause problems in inheritance in biological father, contrary to the customary law of Bali, girls may prefer not to marry. The attitude of the indigenous peoples of Bali pros and cons of the legal culture of society. Conclusion: Its meaning is to give children the right to marry outside the same as children born within marriage. Balinese customary law community in general have not been aware of the Constitutional Court. Balinese people’s attitudes towards the Constitutional Court ruling pro and cons.
Keywords: constitutional court ruling, beyond mating child, ttitude indigenous people of Bali